Poverty Reduction in Cameroon by Korea’s ODA Policy Frame-work: A Search for a New Paradigm - NJILLA, Stephen Njissic (The Graduate School, Ajou University, 2011)
Many have been helpful but a few have been so passionate and committed to see me go through successfully during my studies in Ajou University (GSIS), South Korea. My beloved wife and kids have been constantly been in touch with me since I left Cameroon. I am very motivated by their love and concern. All my Course Masters kept on pressing on one issue, to wit: ‘in order to make this Paper fit into the world of the Academia, show us your Guiding Questions and Key concepts. What are your arguing-points and your source of information?’ This question sounds easy but difficult to come by. But as I struggled, along with their powerful “brainstorming” classes and supervision, the whole Course Work became impacted in me. I am ending the MA Program, with a determination to go back to my country and promote International development and cooperation thanks to them, especially my Thesis Supervisor Prof. Iain Watson, who came and rescued me from the pit of my frustrating moments in life- an ugly scenario not worth recounting here. My course mates, Cameroonians and Korea friends (especially TV, Greg and Ndeh) are not left out. They have all been of great help. I equally thank the Ajou University Administrative Body for providing me with a conducive study environment and providing me the opportunity to attend many International Conferences that have helped to prepare me for the job market. In this light, I respectfully give special thanks to my Departmental Chairman and Lecturer, Prof. Hyoung-wook Jeong and the Associate Director Mrs. Jae-Eun Kim, for all the wonderful moral support they gave me. I owe you all an enormous debt, as I bear sole responsibility for any shortcomings in this Thesis.
학위논문(석사)--아주대학교 국제대학원--국제개발협력과,2011. 2
Keywords: Poverty Reduction in Cameroon; Korea’s ODA Policy Frame-work